Effectiveness Of Management Of Basic Educational Institutions At SDN 1 Kurungrejo And MI Al Azhar, Prambon District, Nganjuk Regency - A. Eidil Fauzi; Akhmad Shunhaji; Abd. Muid N (STIT Attaqwa, 2023)
This research aims to analyze and describe the effectiveness of management of basic education institutions at SDN 1 Kurungrejo and MI Al Azhar. This research uses a descriptive qualitative approach. Data collection uses interviews, documentation studies and observations. The main informant in this research is the Head of the Madrasah and other informants are teachers. Based on the research findings, it can be concluded that; First, the management of educational institutions has been carried out by the two schools through the following steps: 1) Program planning; namely determining the goals or targets to be achieved and determining the paths and resources needed to achieve the goals effectively and efficiently in managing education. Where program planning includes determining the school's vision, mission, goals and work plans 2) Program implementation; namely the implementation of the school work plan covering all areas of school operational implementation which are organized and managed by the educational unit formed in the school/madrasah organizational structure. These fields include: student affairs, curriculum, educators and education personnel, finance and financing, infrastructure, culture and school climate, and public relations (public relations). 3) Program Monitoring and Evaluation; namely the process of monitoring activities to ensure that all organizational activities are carried out as planned and at the same time it is also an activity to correct and improve if deviations are found that will interfere with achieving goals. Second, the school principal as a supervisor plays a very important role in planning, implementing and evaluating school programs. Third, SDN Kurungrejo, which is actually a state school under the auspices of the government, cannot be flexible in managing education, while MI Al Azhar, which is a private school under the auspices of a foundation, can be flexible in managing its education in accordance with predetermined program plans. Ultimately, the effectiveness of educational institutions in managing their institutions has an impact on the quantity of new students each year.